Edukasi Pemanfaatan Cagar Budaya Kabupaten Cilacap Melalui Program Sporturism Tahun 2022 - Dian Imam Saefulah; Kusmiyati; Untung Nugroho (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2022)
Education on the use of cultural heritage in Cilacap Regency through the sporturism program is a sports activity that combines and introduces tourism in a country or region. The use of cultural heritage in Cilacap Regency has great potential in various fields including Sporturism. According to previous research conducted by UNSIL, Cilacap Regency has 82 cultural heritage sites that have been inventoried by the Cilacap Regency Youth Sports and Tourism Service. STKIP Darussalam created this educational activity to increase the knowledge of the people of the Cilacap Regency regarding cultural heritage in the Cilacap area. This educational activity can be carried out through collaboration between the person in charge, PJKR students, tourist visitors, and the community around Fort Pendem, Cilacap Regency. This educational activity was carried out well as seen from the enthusiasm and interest of the community in educational activities on the use of cultural heritage in the Cilacap Regency area.